Practical management plan for invasive mosquito species in Europe: I. Asian tiger mosquito (Aedes albopictus) - Bellini, Romeo; Michaelakis, Antonios; Petrić, Dušan V.; Schaffnerd, Francis; Alten, Bülent; Angelini, Paola; Aranda, Carles; Becker, Norbert; Carrieri, Marco; Di Luca, Marco; Fălcuţă, Elena; Flacio, Eleonora; et al. (My University, 2020)
Aedes albopictus, also known as the “Asian Tiger Mosquito”, is an invasive mosquito species to Europe causing high concern in public health due to its severe nuisance and its vectorial capacity for pathogens such as dengue, chikungunya, yellow fever and Zika. Consequently, the responsible authorities implement management activities to reduce its population density, possibly to below noxious and epidemiological thresholds. In urban areas, these aims are difficult to achieve because of the species’ ability to develop in a wide range of artificial breeding sites, mainly private properties. This document (Management Plan) has been structured to serve as a comprehensive practical and technical guide for stakeholders in organizing the vector control activities in the best possible way. The current plan includes coordinated actions such as standardized control measures and quality control activities, monitoring protocols, activities for stakeholders and local communities, and an emergency vector control plan to reduce the risk of an epidemic.
Keywords: Insecticide; Aedes albopictus; Chikungunya; Community participation; Dengue; Emergency treatment; Europe; Infection control; Insecticide resistance